DEVELOPING A DIGITAL FLIPBOOK FOR FACILITATING READING ACTIVITY IN AN INCLUSIVE CLASS : An Innovative Approach to Enhance Reading Activity in Inclusive Education - Ketut Septia Anyawati; Prof.Dr. I G A Lokita Purnamika Utami, S.Pd., M.Pd,; I Ketut Trika Adi Ana (Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Mahasaraswati Denpasar, 2026)
This research focuses on developing and validating a digital flipbook designed to enhance reading comprehension for sixth-grade students in inclusive classrooms, particularly those with special needs, such as students who are deaf or mute. Utilizing the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model, the study addresses the challenges faced by inclusive students in accessing reading media as material by incorporating accessibility features like sign language, subtitles, visuals, and animations. The research employed various instruments, such as a guide for interviews aimed at assessing needs, a separate interview guide for educators, another for students, a journal maintained by the researcher, a tracking sheet for product development progress, evaluations by content experts, assessments by media experts, and a questionnaire evaluating practicality. The digital flipbook was evaluated by content experts who rated it 4.75 out of 5, and media design experts who scored it 4.60 out of 5, both indicating a